Can physical activity attenuate the impact of internet addiction on anxiety in young adults? A moderation analysis - Adekola B. Ademoyegun; Adebukola G. Ibitoye; Joshua Afolabi; Opeyemi A. Idowu; Henrietta Fawole; Taofeek O. Awotidebe; Chidozie E. Mbada (Journal of Affective Disorders Reports, 2024)
Background: The potential moderators of the nexus between internet addiction (IA) and symptoms of anxiety are less understood. This cross-sectional study aimed to assess the moderating roles of physical activity (PA) and gender in the association between IA and anxiety. Methods: A cross-sectional study of 510 Nigerian undergraduate students was carried out. IA, anxiety, and PA levels (low, moderate, and high) were assessed using Internet Addiction Test, anxiety sub-scale of Depression Anxiety Stress Scale-21, and Patient-Centered Assessment and Counseling for Exercise Plus Nutrition, respectively. Moderation analysis was applied while controlling for important covariates. Results: The mean age of the respondents was 21.33 ± 2.63 years. The prevalence of IA and anxiety was 57.6 % and 52.6 %. IA was positively associated with anxiety (b=0.307, 95 % CI: 0.2168-0.3982, t (498) =6.660, p < 0.001). PA level, but not gender seem to moderate the association between IA and anxiety (F (2, 498) =3.561, p=0.029, R2 change =0.011). Moreover, interaction between PA and gender indicated that the moderating effect of PA was less pronounced among females compared with males (F (3, 498) =2.895, p=0.035, R2 change =0.014). Conclusions: PA can attenuate the deleterious nexus between IA and anxiety in young adults. The attenuation of PA in IA-anxiety nexus is weaker among female young adults compared with male counterparts. PA is a viable low-cost intervention strategy in combating the effect of IA on symptoms of anxiety among young adults. Further longitudinal and experimental studies are needed to better understand the underlying mechanisms among IA, anxiety symptoms, PA, and gender.